Erythrocyte pyridoxamine phosphate oxidase activity: a potential biomarker of riboflavin status? - Mushtaq, Sohail; Su, Han; Hill, Marilyn HE; Powers, Hilary J (The American journal of clinical nutrition, 2009)
BACKGROUND: Riboflavin status is commonly measured by the in vitro stimulation of erythrocyte glutathione reductase with flavin adenine dinucleotide and expressed as an erythrocyte glutathione reductase activation coefficient (EGRAC). However, this assay is insensitive to poor riboflavin status in subjects with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Because G6PD deficiency is common in parts of the world where ariboflavinosis is endemic, it is important to have a measure of riboflavin status that is unaffected by differences in G6PD status. OBJECTIVE: The objective was to further develop and validate a fluorometric assay for pyridoxamine phosphate oxidase (PPO) activity as a measure of riboflavin status. DESIGN: A fluorometric assay was optimized for the flavin-dependent enzyme PPO in erythrocytes. Hemolysates from a previous riboflavin intervention study (2- and 4-mg riboflavin supplements) were used to investigate the responsiveness of the method to changes in riboflavin intake. RESULTS: PPO activity and the PPO activation coefficient (PPOAC) were used to assess riboflavin status. Both PPO activity and PPOAC responded to riboflavin supplements (P < 0.01), but only PPO showed a dose response (P < 0.001). The change from baseline to after the intervention in PPOAC and PPO enzyme activity was significantly inversely correlated (P < 0.001). Both PPO activity and PPOAC were strongly correlated with EGRAC (P < 0.001). Additionally, both PPOAC and EGRAC showed a significant inverse correlation with dietary riboflavin intake (P < 0.01); PPO activity was positively correlated with riboflavin intake (P < 0.01). CONCLUSION: PPO activity could be used as a biomarker for measuring riboflavin status, especially in populations with a high prevalence of G6PD deficiency. This trial is registered at www.isrctn.org as ISRCTN35811298.